2010
DOI: 10.1016/j.ijid.2009.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Incidence trends of viral hepatitis A, B, and C seropositivity over eight years of surveillance in Saudi Arabia

Abstract: Despite the declining trend over the eight-year period, viral hepatitis, especially that caused by HBV and HCV, remains a major public health problem in Saudi Arabia, and has probably been underestimated in previous reports. There is a need for more comprehensive prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 15 publications
3
59
1
Order By: Relevance
“…Most of our patients were Saudis, and this finding is consistent with the national data showing high prevalence of CHB among Saudis compared to non Saudis in the country [8,10]. Patients with HBeAg negative CHB were more likely to be older than HBeAg positive patients, which may be related to the natural history of vertically transmitted CHB and HBeAg sero-conversion over the years as the disease progresses from the immune-active phase to the active hepatitis B carrier stage [2][3][4]28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most of our patients were Saudis, and this finding is consistent with the national data showing high prevalence of CHB among Saudis compared to non Saudis in the country [8,10]. Patients with HBeAg negative CHB were more likely to be older than HBeAg positive patients, which may be related to the natural history of vertically transmitted CHB and HBeAg sero-conversion over the years as the disease progresses from the immune-active phase to the active hepatitis B carrier stage [2][3][4]28].…”
Section: Discussionsupporting
confidence: 92%
“…Previously reported data on CHB from Saudi Arabia have focused on the prevalence of the disease [5][6][7] and the effect of HBV vaccination on reducing the rate of hepatitis B surface antigen (HBsAg) seropositivity in the country [9,10], but there are no similar data available that focus on the long-term follow-up or treatment outcome. HBV-DNA was found to be the best predictor of the severity of fibrosis, long-term outcome, progression to end-stage liver disease, the risk of hepatocellular carcinoma (HCC) and the response to therapy [2,3,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that males have a 1.8 greater likelihood [35] of HBV infection and that HBV occurs at a higher incidence in males than in females [15]. Therefore, studies among blood donors may not accurately reflect the situation in the general community but rather may overrate HBV carrier rate and prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the year 2007, 9,000 newly diagnosed viral hepatitis cases were reported by the Saudi Ministry of Health, ranking viral hepatitis as the second-most common viral disease after chickenpox [14], with about 50% of the cases were due to HBV and over 30% due to HCV [15]. In Saudi Arabia HIV rates of 1.5 cases per 100,000, Saudis, and 13.2 per 100,000 non-Saudi residents [16], and a prevalence of 0.0% to 0.4% of anti-HTLV-I/II been reported [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Its peaks in March and September. 13 Hepatitis A virus infection is an acute disease and can be cured and all of the transmission of HAV through the fecal-oral route.…”
Section: Methodsmentioning
confidence: 99%